Dendropanax morbifera Leaf Polyphenolic Compounds: Optimal Extraction Using the Response Surface Method and Their Protective Effects against Alcohol-Induced Liver Damage - Taekil Eom; Kyeoung Cheol Kim; Ju-Sung Kim (MDPI AG, 2020)
The response surface methodology was used to optimally extract the antioxidant substances from Dendropanax morbifera leaves. The central composite design was used to optimally analyze the effects of ethanol concentration, sample to solvent ratio, extraction temperature, and extraction time on the total flavonoids (TF) content, ferric reducing antioxidant power (FRAP), and Trolox equivalent antioxidant capacity (TEAC). All three parameters were largely influenced by the ethanol concentration and extraction temperature, while TEAC was also influenced by the sample to solvent ratio. The maximum values of TF content, FRAP, and TEAC were achieved under the following extraction conditions: 70% ethanol, 1:10 sample to solvent ratio, 80 °C, and 14 h. The D. morbifera leaf extracts (DMLE) produced under these optimum extraction conditions were investigated to determine their preventive effects on alcohol-induced liver injury. The DMLE was shown to prevent liver injury by scavenging the reactive oxygen species generated by alcohol. In addition, composition analysis of DMLE found high contents of chlorogenic acid and rutin that were determined to inhibit alcoholic liver injury. The findings of this study suggest that DMLE could prove useful as a functional food product supplement to prevent liver injury caused by excessive alcohol consumption.